GUI MATLAB UNTUK METODE FUZZY SAW DAN FUZZY TOPSIS DALAM PEMILIHAN PENERIMA BEASISWA PPA DENGAN PEMBOBOTAN ENTROPI (Studi Kasus : Pemilihan Penerima Beasiswa PPA tahun 2017 Mahasiswa FSM UNDIP, Semarang) - Rahmaniar, Ratna; Widiharih, Tatik; Ispriyanti, Dwi (Jurnal Gaussian, 2018)
For students, scholarships are important to ease the burden on parents, namely tuition fees.The large number of scholarship applicants is a challenge for FSM to be able to provide an appropriate, effective and efficient decision to manage data on scholarship recipients who are truly entitled to receive scholarships. Prospective scholarship recipients are selected based on the criteria determined by FSM.The criteria determined by the FSM are GPA (Grade Point Average), parent income, number of certificates, number of dependents of parents, semester, and electricity. The method applied to select 170 PPA scholarship recipients (Academic Achievement Improvement) is FSAW (Fuzzy Simple Additive Weighting) and FTOPSIS (Fuzzy Technique for Order Preference by Similarity to Ideal Solution) with entropy weighting. This entropy weighting does                                             a combination of the initial weight that has been determined by FSM and the calculation weight. This research was conducted with the help of MATLAB (Matrix Laboratory)  GUI (Graphical User Interface) as a computing tool. With the MATLAB GUI system built, it can simplify and speed up the selection process. FSAW and FTOPSIS calculation results are 96% the same, while FSAW with FSM is only 39% the same and FTOPSIS with FSM is only 42% the same.The FSAW and FTOPSIS methods are better used than the determination of the FSM, because the results of the FSM are not appropriate.FSM selects manually by looking at files collected by registrants. Keywords:Scholarship, FSAW, FTOPSIS, Entropy, GUI